Вы находитесь на странице: 1из 14

.

17 2011

.
.

.
.


f (x) [a, ).
Rb
f (x) dx
a

b, b . ,
Z

f (x) dx = lim

Zb

f (x) dx.

, f (x) = 1/(x 2 ),
Zb
1

b
dx
1
1
=

=1 ,
x2
x 1
b
.

Z
1



dx
1
=
lim
1

= 1.
b
x2
b

.
.

y
3

y=

3
x2

Z
1

2
.

3
dx = 3
x2
x
4

.
.


,
f (x), ,
.
. f (x) ,
, +, ..
+
Z
f (x) dx = +.
a


+
Z
f (x) dx < +.
a

.
.

.
,
Z
cos x dx = lim sin b.
b

, , sin b .

.
.


Zb

f (x) dx = lim

Zb

f (x) dx.

,
+
+
Z
Z0
Z
f (x) dx =
f (x) dx +
f (x) dx.

.
.

F (x) f (x) [a, +).


Z
a



f (x) dx = lim F (x) F (a) = F (x) .
x
a

.
.



, ,

:
Z
1


 Z0
Z1/e
ex dx
dt
t dt
dt
x
= e = t, x = ln t, dx =
=
=
.
x
t
t ln t
ln t
1/e

0 = lim t = lim ex .
x
, ,
,
.
.

.
.

x=1
Z

dx
< , p > 1
xp
dx
= , p 1
xp

x=1

.
.

f (x) dx f (x).

f (x) g(x) ,
[a, ). f (x) g(x) .

+
Z
g(x) dx < +,
a

f (x) dx ,

+
+
Z
Z
f (x) dx
g(x) dx.
a

.
.

f (x) g(x) ,
[a, ).
C = lim

R
a

g(x) dx ,

f (x)
g(x)

f (x) dx .

.
.


f (x) ,
.

|f (x)| g(x), a x ,
+
Z
g(x) dx < +.
a

+
R

f (x) dx .


.
[a, b] ( (a, b)),
,
Rb
f (x) dx .
a

,

. ,
Zb

f (x) dx = lim

Zb

0
a+

f (x) dx.